Adding Autonomic Healing Capabilities to Polyethylene Oxide. Issue 1 (13th August 2012) - Chipara, Dorina Magdalena; Flores, Maritza; Perez, Alma; Puente, Nancy; Lozano, Karen; Chipara, Mircea
Abstract The addition of autonomic healing (frequently defined as self‐healing) capabilities to a water‐soluble polymer (polyethylene oxide, PEO) is for the first time reported. The self‐healing system consists of urea‐formaldehyde microcapsules filled with dicyclopentadiene and first‐generation Grubbs catalyst, dispersed within polyethylene oxide. Raman spectroscopy, optical microscopy, electron microscopy, and thermogravimetric analysis were used to characterize this autonomic healing system. Self‐healing capabilities were confirmed by mechanical testing (load–displacement, engineering stress–engineering strain, and true stress–true strain dependences) recorded at very slow elongation rates (0.01 mm/s). The testing fate was chosen to allow for the complete consumption of the monomer before fracture (the polymerization kinetics of PEO was estimated from Raman measurements). © 2012 Wiley Periodicals, Inc. Adv Polym Techn 32: E505–E513, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/adv.21296